Effect of Long-Term Frozen Storage on Health-Promoting Compounds and Antioxidant Capacity in Baby Mustard - Zhang, Fen; Zhang, Jiaqi; Di, Hongmei; Xia, Pingxin; Zhang, Chenlu; Wang, Zihan; Li, Zhiqing; Huang, Shuya; Li, Mengyao; Tang, Yi; Luo, Ya; Li, Huanxiu; et al. (Frontiers in Nutrition, 2021)
This study investigated the effects of blanching and subsequent long-term frozen storage on the retention of health-promoting compounds and antioxidant capacity in frozen lateral buds of baby mustard. Results showed that all glucosinolates were well preserved during frozen storage, and 72.48% of total glucosinolate content was retained in the unblanched treatment group after eight months, as were chlorophylls, carotenoids, ascorbic acid, total phenolics, soluble sugars, soluble proteins, and antioxidant capacity. The loss of nutritional qualities mainly occurred in the first month of frozen storage, and nutritional qualities in the unblanched treatment group were significantly better than those in the blanched treatment group during frozen storage. Blanching before freezing reduced contents of high-content glucosinolates and ascorbic acid, as well as antioxidant capacity levels. Therefore, we recommend using long-term frozen storage to preserve the quality of baby mustard to achieve annual supply, and freezing without blanching.